The age of mass migration in Latin America - Blanca Sánchez-Alonso (European Historical Economics Society (EHES), 2018)
The experiences of Latin American countries are not fully incorporated into current debates concerning the age of mass migration even though 13 million Europeans migrated to the region between 1870 and 1930. This paper draws together different aspects of the Latin America immigration experience. Its main objective is to rethink the role of European migration to the region, addressing several major questions in the economics of migration: whether immigrants were positively selected from their sending countries, how immigrants assimilated into the host economies, the role of immigration policies, and the long-run effects of immigration. Immigrants came from the economically backward areas of Southern and Eastern Europe, yet their adjustment to the host labour markets in Latin America seems to have been successful. The possibility of rapid social upgrading made Latin America attractive for European immigrants. Migrants were positively selected from origin according to literacy. The most revealing aspect of new research is showing the positive long-run effects that European immigrants had in Latin American countries. The political economy of immigration policies deserves new research, particularly for Brazil and Cuba. The case of Argentina shows a more complex scenario than the classic representation of landowners constantly supporting an open-door policy.
Keywords: N36; O15; J61; 330; Historical migration; Latin America; Immigrants' selection; Socioeconomic impact